Electrical properties and phase transition of Ba(Zr0.05Ti0.95)1 - X(Fe0.5Ta0.5)xO3ceramics - C. Kruea-In (2018)
© 2015 Elsevier Ltd. All rights reserved. In this work, properties of Ba(Zr0.05Ti0.95)1 - x(Fe0.5Ta0.5)xO3ceramics with 0.00x 0.07 were investigated. The ceramics were fabricated by a solid state reaction technique. X-ray diffraction analysis indicated that all samples exhibited single phase perovskite. Examination of the dielectric spectra revealed that the Fe and Ta additives promoted a diffuse phase transition, and the two phase transition temperatures, as observed in the dielectric curve of pure Ba(Zr0.05Ti0.95)O3, merged into a single phase transition temperature for higher x concentrations. The transformation was confirmed by ferroelectric measurements. In addition, the doped ceramics exhibited high relative dielectric tunability, especially for higher x concentration samples.